Case Study Of Effectiveness Of E-Learning (E-Sprint) In Universiti Putra Malaysia (UPM) - Md Jaafar, Fauziah (2007)
UPM is playing a vital role in changing its strategy to adopt e-lerning technology and maintain its highly position and reputation in the education industry. The case study identifies both external and internal factors that affect either directly or indirectly the teaching and learning environment in UPM.